Restorative Justice Sebagai Penyelesaian Tindak Pidana Malpraktek Dokter Pada Polda Jawa Timur - Sulianto Sulianto; Wahyu Prawesthi; Moh. Taufik; Syahrul Borman (JOURNAL OF SHARIA ECONOMICS, 2022)
Health is one of the basic human rights guaranteed by the state as regulated in Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia, in carrying out their duties, medical personnel, especially doctors, have a vital role in providing quality health services to the community. However, in practice, it is not uncommon for medical errors to occur which lead to allegations of malpractice crimes, for this reason a study was conducted on the Regulation of Restorative Justice as an Alternative to Settling Criminal Acts of Doctors' Malpractice and the justice and impact of Restorative Justice on the Medical profession, this study uses the Normative Juridical research method with three approaches, the Statute Approach, the Conceptual Approach, and the Case Approach, namely the Medical Malpractice case that has been reported by the Victim with a Public Complaint Report handled by the East Java Regional Police, for the report the doctor as the accused party made peace efforts facilitated by the East Java Regional Police investigators, at the request of the Reported Party the investigator made efforts to examine the material and formal requirements to continue the Restorative Justice efforts